Compliance with follow‐up and adherence to medication in hypertensive patients in an urban informal settlement in Kenya: comparison of three models of care. Issue 7 (3rd July 2018) - Kuria, Ng'endo; Reid, Anthony; Owiti, Philip; Tweya, Hannock; Kibet, Caleb Kipkurui; Mbau, Lilian; Manzi, Marcel; Murunga, Victor; Namusonge, Tecla; Kibachio, Joseph
Abstract: Objective: To determine and compare, among three models of care, compliance with scheduled clinic appointments and adherence to antihypertensive medication of patients in an informal settlement of Kibera, Kenya. Methods: Routinely collected patient data were used from three health facilities, six walkway clinics and one weekend/church clinic. Patients were eligible if they had received hypertension care for more than 6 months. Compliance with clinic appointments and self‐reported adherence to medication were determined from clinic records and compared using the chi‐square test. Univariate and multivariate logistic regression models estimated the odds of overall adherence to medication. Results: A total of 785 patients received hypertension treatment eligible for analysis, of whom two‐thirds were women. Between them, there were 5879 clinic visits with an overall compliance with appointments of 63%. Compliance was high in the health facilities and walkway clinics, but men were more likely to attend the weekend/church clinics. Self‐reported adherence to medication by those complying with scheduled clinic visits was 94%. Patients in the walkway clinics were two times more likely to adhere to antihypertensive medication than patients at the health facility (OR 1.97, 95% CI 1.25–3.10). Conclusion: Walkway clinics outperformed health facilities and weekend clinics. The use of multiple sites for the management of hypertensive patients led to good compliance with scheduled clinic visits and very good self‐reported adherence to medication in a low‐resource setting.